Post-referendum Negotiations, Special Session on Security Option Paper on Joint Command Mechanism for the Two Areas (Tufts Archival Research Center, 2005)
This document is about the Joint Command Mechanism (JCM) that includes both the Sudanese Armed Forces and the Sudan People's Liberation Army. It is also about the tasks, the objective, membership, and the finances of the command.